Efek Promosi, Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen - Reza Safitri , Mandataris (STIA Indragiri, 2017)
ABSTRACKThe purpose of this study was to analyze the effect of promotions, price and quality of service to customer satisfaction PT. Arthabuana Margausaha Finance Branch Batam. The variables in this study include the independent variables are promotional (X1) price (X2) quality of service (X3) and the dependent variable is customer satisfaction (Y). The formulation of the problem in this study is whether the promotion, pricing and service quality effect on customer satisfaction PT. Arthabuana Margausaha Finance Branch Batam.This research uses quantitative data derived from primary data collected through questionnaires. The population in this study are all consumers PT. Arthabuana Margausaha Finance Branch of Batam as many as 219 people and sampling using the formula Slovin with a standard error of 5% or 0.05 obtained as many as 142 people. The data analysis method used is the test instrument testing done by testing the validity and reliability. Data were analyzed using descriptive analysis, multiple linear regression analysis and hypothesis testing.The results showed that in partial sale have significant effects on consumer satisfaction with t values of 7136 and the value of the probability of 0000, prices have a significant effect on consumer satisfaction with t values of 5607 and the value of the probability of 0000, the service quality has a significant effect on satisfaction consumers with t values of 2,753 and a probability value of 0.007. And the results of testing the simultaneous promotion, pricing and service quality has a significant effect on consumer satisfaction with F value of 96 321 and a probability value of 0.000. Keywords: Promotion, Price, Service Quality, Customer Satisfaction